COMPOSITION AND OCCURRENCE OF THE GRANDISPORA MACULOSA ZONAL ASSEMBLAGE (MISSISSIPPIAN) IN THE SUBSURFACE OF THE CARNARVON BASIN AND THE COOLCALALAYA SUB-BASIN OF WESTERN AUSTRALIA, AND ITS GONDWANAN DISTRIBUTION (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2017)
The Grandispora maculosa miospore assemblage – initially described in 1968 from Middle-Late Mississippian strata of New South Wales (eastern Australia) – is well represented in samples examined herein from 10 Western Australian subsurface sections located in the northern Perth Basin (Coolcalalaya Sub-basin) and, to its immediate north, in several sub-basins of the southern and northern sectors of the Carnarvon Basin. Of particular stratigraphic-correlative importance is the presence of the eponymous G. maculosa together with, inter alia, Reticulatisporites magnidictyus, Verrucosisporites quasigobbettii, V. gregatus, Apiculiretusispora tersa, Raistrickia accinta, R. radiosa, Foveosporites pellucidus, and Cordylosporites asperidictyus. Four species are newly described herein: Apiculatasporites spiculatus, Dibolisporites sejunctus, Raistrickia corymbiata, and Vallatisporites valentulus. Published accounts from elsewhere in Gondwana collectively signify the widespread dissemination of the G. maculosa palynoflora, particularly through northern and western regions of the supercontinent, thus affording an effective means of intra-Gondwanan stratal correlation. Limited absolute dating and stratigraphic-successional considerations across Gondwana indicate that the age of the G. maculosa Assemblage can be bracketed within the middle Visean-early Serpukhovian of the Middle-Late Mississippian. This age is supported by the complete absence of bilaterally symmetrical, non-striate, saccate pollen grains, produced by walchian conifers, which were introduced globally (including in Australia) and near-synchronously late in the Serpukhovian. Cryptogamic land plants (ferns, articulates, lycophytes) are the inferred source of the palynoflora.